KESULITAN BELAJAR YANG DIHADAPI OLEH MAHASISWA DAN SOLUSINYA - Mohammad Liwa Irrubai (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2014)
One of the problems in the world of education in Indonesia highlighted that many people are of quality problems or quality. Quality of education is of course related to learning. However, reality shows that  a lot of the students did not achieve expected maximum learning because there are several factors that influence them, which are; the influence of close friends, economic status, encouragement of parents, facilities and infrastructure. On the other hand the dynamics of what happens to the students showed clearly the tendency of students to disinterest in science studies. This paper presented: a. Difficulty in learning influenced by; 1) internal factors; intelligence factors and interest, 2) external factors; family and community factors. While solutions to reduce the difficulty of learning are as follows; 1) provides tutoring, 2) generate interest in students to learn the lessons that follow, 3) information service, 4) placement services, and 5) counseling services.